High-Efficient Low-Cost Photovoltaics Recent Developments - Petrova-Koch, Vesselinka; Hezel, Rudolf; Goetzberger, Adolf; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
A bird's-eye view of the development and problems of recent photovoltaic cells and systems and prospects for Si feedstock is presented. High-efficient low-cost PV modules, making use of novel efficient solar cells (based on c-Si or III-V materials), and low cost solar concentrators are in the focus of this book. Recent developments of organic photovoltaics, which is expected to overcome its difficulties and to enter the market soon, are also included.
Milestones of Solar Conversion and Photovoltaics -- From Extraterrestrial to Terrestrial Applications -- PV Solar Electricity: From a Niche Market to One of the Most Important Mainstream Markets for Electricity -- Advanced Solar-Grade Si Material -- EFG Ribbon Technology -- A Novel High-Efficiency Rear-Contact Solar Cell with Bifacial Sensitivity -- Commercial High-Efficiency Silicon Solar Cells -- III-V Solar Cells and Concentrator Arrays -- The Economic Perspective: Is Concentrator PV Capable of Breaking the Economic Barrier -- Fluorescent Solar Energy Concentrators: Principle and Present State of Development -- Hybrid Photovoltaic/Thermal Collector Based on a Luminescent Concentrator -- Installation Concept and Future Applications -- Design Rules for Efficient Organic Solar Cells.
Keywords: Physics; Lasers; Photonics; Optics; Optoelectronics; Plasmons (Physics).; Engineering; Optical materials; Electronic materials; Physics; Laser Technology, Photonics; Optics, Optoelectronics, Plasmonics and Optical Devices; Engineering, general; Optical and Electronic Materials; Electronic books